Recent trends in risk factors of ectopic pregnancy: a retrospective study at a tertiary care centre - Singh, Nikita; Naagar, Jagrati Kiran; Pandey, Mohita; Lokhande, Harshali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Ectopic pregnancy occurs when a fertilized ovum implants at a site outside the uterine cavity. Methods: A retrospective study was conducted in patients of ectopic pregnancy at a tertiary care centre. All ectopic pregnancies reported during this time period were selected and case sheets were analysed. The risk factors causing the ectopic pregnancies were obtained by clinical history and physical examination mentioned in case sheets. A menstrual practice questionnaire (WHO) was filled telephonically to assess menstrual hygiene practices in our patients of ectopic pregnancy. Results: Risk factors found in our study were age group 21-30 years, multiparity, previous tubal surgeries, low socioeconomic status, past history of PID and poor menstrual hygiene. Conclusions: PID stands out as the most modifiable risk factor. Awareness for the same among adolescents, sexually active females and newlywed couples may prove of paramount importance to reduce the incidence of ectopic pregnancy in long term.